UREA TOXICITY STUDY IN RADISH AND CABBAGE GERMINATION - Souza, D. S. S.; Ramos, J. L.; Dias, A. B.; Portela, A. L. R.; Villa, F. B.; Godoy, G. B.; Cristiano, G. A.; Godoi, I. R. G.; Monteiro, J. O. F.; Gabriel, L.; et al. (Revista Brasileira de Engenharia de Biossistemas, 2019)
Urea is widely used as a fertilizer in agriculture. However, at certain concentrations, it may present significant toxicity. This work aimed to evaluate the behavior of urea as a stressor in seed germination of Raphanus sativus L. (radish) and Brassica oleracea L. (cabbage), finding the NOEC (No Observed Effect Concentration), LOEC (Lowest Observable Effect Concentration) and EC50 (Effective Concentration) for each species. The experiments were performed by preparing a culture medium with a solution containing macro and micro nutrients in optimized concentrations and dissolved agar, besides concentrations of urea were also added. To the pH values control of the culture medium, two types of buffer solutions were used: pH 7.0 for radish studies, and 7.5 for cabbage. In relation to radish, was observed that NOEC appeared in 20.0 mg L-1 of stressor, LOEC in 30.0 mg L-1 and EC50 in 183.0 mg L-1. For cabbage, NOEC appeared in 1.0 mg L-1 of stressor, LOEC in 2.0 mg L-1 and EC50 in approximately 418.0 mg L-1. With these data, it can be noted that cabbage had higher sensitivity in chronic toxicity assessments (NOEC/LOEC) and radish, higher sensitivity in acute toxicity assessments (EC50).